PENGARUH SUHU TERHADAP KANDUNGAN FENOLIK TOTAL DAN AKTIVITAS ANTIOKSIDAN BAWANG PUTIH BUBUK DAN BAWANG HITAM BUBUK - Ika Novianti Safitri; Nuniek Herdyastuti (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2021)
Black garlic is a fresh garlic product that has been heated for two weeks at a controlled temperature (65-90oC). Black garlic has a different color, smell, and taste than fresh garlic. High moisture content of garlic and black garlic make these foods spoil easily. Oven drying techniques can extend the shelf life of garlic. The purpose of this research is to determine the effect of drying temperature on total phenolic content and antioxidant activity of garlic powder and black garlic powder. Garlic and black garlic are to be dried at 60, 70, 80, and 90oC. Total phenolic content was determined by Folin-Ciocalteu reagent and antioxidant activity was measured by 2,2-diphenyl-1-picryhydrazyl (DPPH) method. The results of this reasearch showed that the best drying temperature for garlic was 60oC which had total phenolic content 0,178 mg gallic acid equivalent (GAE)/g and moderate antioxidant activity with IC50 value 105.01 ppm; while the best drying temperature for black garlic was 80oC which had total phenolic content 2.957 mg gallic acid equivalent (GAE)/g and strong antioxidant activity with IC50 value 67.32 ppm. Key words: black garlic, garlic, phenolic, antioxidant